The Effect Of Using Picture Media To Improve Students' Motivation In Writing Descriptive Text - Rambe, Hanifa (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
Based on the researcher observation, it was found that such as some of students less motivation in writing. The major of the problem faced by them was Some students did not feel motivated to developed ideas for their writing. Then the researcher does the treatment by using Picture Media only in experiment class, and using conventional teaching in control class. Finally, the researcher gave post-test to both classes to know the different effect output score test between experiment class and control class. The technique of data collecting was a test and questionnaire. The technique of data analyzing data, the researcher used sample paired t-test formula by using SPSS 22. After analyzing the data, the researcher found that there is a significant effect of using Picture Media to improve students’ motivation in writing